Handwriting measures as reflectors of executive functions among adults with Developmental Coordination Disorders (DCD) - Rosenblum, Sara (Frontiers in Psychology, 2013)
Planning ahead and organizational abilities in time and space are ingredients of high-level cognitive functions labelled as ‘Executive Functions’ (EF) required for daily activities such as writing or home management. EF deficits are considered a possible underlying brain mechanism involved in Developmental Coordination Disorders (DCD). The aim of the study was to compare the handwriting process measures and the planning and organizational abilities in space and time of students with DCD with those of matched controls and to find whether handwriting measures can predict daily planning and organizational abilities among students with DCD. Method: 30 students diagnosed with DCD, between the ages of 24-41, and 30 age- and gender-matched controls participated in the study. They filled out the Handwriting Proficiency Screening Questionnaire (HPSQ) and the Adult Developmental Co-ordination Disorders Checklist (ADC). Furthermore, they copied a paragraph on a digitizer that is part of a computerized system (ComPET). Results: Significant group differences were found for the HPSQ subscales scores as well as for the temporal and spatial measures of the paragraph copy task. Significant group differences were also found for the planning and organizational abilities in space and time as reflected through the ADC subscales. Significant medium correlations were found in both groups between the mean HPSQ time subscale and the ADC-B subscale mean score (r=.50 /.58 p<.05). Series of regression analyses indicated that two handwriting performance measures (mean HPSQ time subscale and mean stroke duration) predicted 19% of planning and organizational abilities as reflected through daily functions (ADC-B) (F (3, 54) = 38.37, β= . 40 p<.0001). Conclusion: The results support previous evidence about EF deficits as an underlying brain mechanism involved in motor coordination disorders, their significance as related to theoretical models of handwriting and daily function among DCD will b